2009
DOI: 10.1093/jac/dkp464
|View full text |Cite
|
Sign up to set email alerts
|

Safety of triazole antifungal drugs in patients with cancer

Abstract: Triazole drugs are widely used in cancer patients for prophylaxis and treatment of life-threatening invasive fungal infections. Fluconazole, available for over two decades, is safe and effective in patients with cancer; however, the excellent safety profile of fluconazole may not be applicable to the newer triazoles. Itraconazole, voriconazole and posaconazole are associated with adverse events, and drug interactions frequently occur, particularly in cancer patients, since the triazoles and many drugs used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 66 publications
2
43
0
1
Order By: Relevance
“…The Cologne group, 10 in contrast, reported no significant intolerance/toxicities associated with posaconazole, perhaps reflecting a higher degree of clinician confidence in the drug even in the presence of mucositis. Serious adverse events were consistent with the recognized toxicities of azoles 18 but for voriconazole, less frequent than post-marketing reports. 19,20 The emergence of resistant fungi is a potential drawback of broad-spectrum antifungal prophylaxis.…”
Section: Discussionsupporting
confidence: 70%
“…The Cologne group, 10 in contrast, reported no significant intolerance/toxicities associated with posaconazole, perhaps reflecting a higher degree of clinician confidence in the drug even in the presence of mucositis. Serious adverse events were consistent with the recognized toxicities of azoles 18 but for voriconazole, less frequent than post-marketing reports. 19,20 The emergence of resistant fungi is a potential drawback of broad-spectrum antifungal prophylaxis.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies, mostly based on data derived from clinical trials, reported a 2%-23% range, depending on the drug of interest and especially the severity of the disease [28] . Clinical evidence on ketoconazole emerged in early 80', when 54 reports of alleged ketoconazoleinduced liver injury submitted to the FDA from the time of initial marketing in 1980, of which 33 were labeled as likely.…”
Section: Antimycotics and Dili: Clinical And Regulatory Aspectsmentioning
confidence: 99%
“…Considering that almost all fungal pathogens isolated during posaconazole PAP were susceptible in vitro to the triazole (unreported data), the possibility of reduced absorption, with sub-therapeutic serum concentrations of posaconazole, must be considered. [23][24][25] Many factors, such as the development of mucositis, impaired dietary intake and use of proton pump inhibitors may cause interindividual pharmacokinetic variability in AML patients, and therapeutic drug monitoring may be required. [23][24][25][26][27][28] Unlike previous studies showing impaired sensitivity of the GM assay in patients on antifungal therapy, 29 in our experience GM retained a major role in the diagnosis of IA also in patients receiving posaconazole.…”
Section: *Three Patients With a Diagnosis Of Invasive Aspergillosis Wmentioning
confidence: 99%
“…[23][24][25] Many factors, such as the development of mucositis, impaired dietary intake and use of proton pump inhibitors may cause interindividual pharmacokinetic variability in AML patients, and therapeutic drug monitoring may be required. [23][24][25][26][27][28] Unlike previous studies showing impaired sensitivity of the GM assay in patients on antifungal therapy, 29 in our experience GM retained a major role in the diagnosis of IA also in patients receiving posaconazole. Assuming that reduced absorption of posaconazole, leading to subtherapeutic serum concentrations, could explain the occurrence of breakthrough IA, normal production and spread of GM by the fungal pathogen in these cases seems to be likely.…”
Section: *Three Patients With a Diagnosis Of Invasive Aspergillosis Wmentioning
confidence: 99%